Comparison of Marginal Adaptation of Different Resin-Ceramic CAD/CAM Crowns: An In Vitro Study. Issue 1 (May 2021) - Oguz, Ece Irem; Kılıçarslan, Mehmet Ali; Özgür, Merve Erdog˘; Orhan, Kaan; Shujaat, Sohaib
Aim: To compare the marginal adaptation of crowns fabricated by using three different resin-ceramic computer-aided design/computer-aided manufacturing (CAD/CAM) materials. Materials and Methods: Crowns fabricated from three different resin-ceramic CAD/CAM blocks, applied on a typodont premolar (#14), were tested with regard to marginal adaptation, in this in vitro study. The typodont maxillary first premolar was prepared to serve as the master die and digitized with an intraoral scanner. The same virtual crown design was used to fabricate all specimens. Forty-eight crowns were fabricated from the same virtual crown design using three different CAD/CAM resin-ceramic blocks as follows ( n = 16): Lava Ultimate (LU), GC Cerasmart (GC), Vita Enamic (VE). Master die and crowns were scanned with a laboratory scanner and three-dimensional data were transferred into three-matic software. The software calculated the mean of the marginal discrepancy (MD) for each crown in negative and positive values, representing under and over estimation of the crown margin, respectively. A marginal discrepancy index (MDI) was obtained for each group using negative and positive MDs. All data were statistically analyzed using one-way analysis of variance and Tukey's honest significance test ( α = 0.05). Results: The analysis of variance showed no statistical differences between materials regarding the negative and positive MDs ( P > .05). The MDI for LU was lower than GC and VE ( P < .05). Conclusion: The marginal adaptation of different resin-ceramic materials was different with regard to MDI values. Nevertheless, the MD values of all groups were within the clinically acceptable range.